2017
DOI: 10.1021/acsnano.7b04361
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotube Reactor for Redox Transformation of Mercury Dichloride

Abstract: Single-walled carbon nanotubes (SWCNTs) possessing a confined inner space protected by chemically resistant shells are promising for delivery, storage, and desorption of various compounds, as well as carrying out specific reactions. Here, we show that SWCNTs interact with molten mercury dichloride (HgCl) and guide its transformation into dimercury dichloride (HgCl) in the cavity. The chemical state of host SWCNTs remains almost unchanged except for a small p-doping from the guest HgCl nanocrystals. The density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 40 publications
2
52
0
1
Order By: Relevance
“…Although very powerful, the effect of CNTs is not limited to templating. Toxic, water-soluble HgCl 2 was transformed into Hg 2 Cl 2 within CNTs, with the latter contributing to the transformation via electron transfer pathways, donating electron density [50]. Functional groups pendant to carbons have also exploited for the same redox reaction [51], with the consequent oxidation of the carbon material.…”
Section: Nanoreactors-reactions Type I and Iimentioning
confidence: 99%
“…Although very powerful, the effect of CNTs is not limited to templating. Toxic, water-soluble HgCl 2 was transformed into Hg 2 Cl 2 within CNTs, with the latter contributing to the transformation via electron transfer pathways, donating electron density [50]. Functional groups pendant to carbons have also exploited for the same redox reaction [51], with the consequent oxidation of the carbon material.…”
Section: Nanoreactors-reactions Type I and Iimentioning
confidence: 99%
“…Despite the fact that many works reported the Raman spectroscopy studies on SWCNTs filled with electron acceptors and common doping‐induced trends in changing Raman modes were revealed, there are only a few reports on the Raman spectroscopy studies of SWCNTs filled with electron donors using a limited number of laser wavelengths. In Refs.…”
Section: Resultsmentioning
confidence: 99%
“…The SWCNTs can be filled with different simple substances, chemical compounds, and molecules possessing appropriate chemical and physical properties. It was demonstrated that metals and some organic and organometallic molecules result in n‐doping of SWCNTs, whereas metal halogenides lead to p‐doping of nanotubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are the reports on the investigation of the electronic properties of SWCNTs filled with MnCl 2 , MnBr 2 [45,46], FeCl 2 , FeBr 2 , FeI 2 [47], CoBr 2 [48], NiCl 2 [49], NiBr 2 [49,50], CuCl [51,52], CuBr [51], CuI [51,53,54], ZnCl 2 [55,56], ZnBr 2 , ZnI 2 [55], RbI, RbAg 4 I 5 [57], AgCl [58][59][60][61], AgBr, AgI [58], CdCl 2 [56,62,63], CdBr 2 , CdI 2 [62], SnF 2 [64], TbCl 3 [56,65,66], TbBr 3 , TbI 3 [66], PrCl 3 [65,67], ErCl 3 [68], TmCl 3 [65,69], and HgCl 2 [70]. The characterization of the electronic properties of the filled SWCNTs was performed by three main techniques: OAS, Raman spectroscopy, and XPS.…”
Section: Electronic Properties Of Metal Halogenide-filled Swcntsmentioning
confidence: 99%